Every 90 seconds: our common cause ending violence against women - DePrince, Anne P. (Oxford scholarship online Psychology, 2022)
In 'Every 90 Seconds', Anne P. DePrince argues that to end violence against women, we must fundamentally redefine how we engage with it - starting by abandoning the idea that such acts are a problem involving only those who abuse or are abused. Instead, DePrince explains how violence against women is inextricably linked to other issues that stoke our greatest passions, including healthcare and education, immigration, economic security, criminal justice reform, and gun control.